Improving English Speaking Skills by Implementing Direct Method on 7th Grade Students of MTs Negeri 5 Bojonegoro - Safa, Aulia Nabilla; Pariyanto, Pariyanto (Sintuwu Maroso Journal of English Teaching, 2023)
Speaking proficiency is the ability of an individual to use oral language to communicate. The direct method is an instructional approach in foreign language teaching where the teacher directly uses the target language as the medium of instruction, without using the students’ native language. The main goal of implementing the direct method is to enhance students’ mastery of the foreign language, particularly in oral communication skills. The design used in this research is quasi experiment with a pre-test and post-test. The technique used to collect data in research is interviews. To determine whether there is an improvement in students’ English-speaking abilities after using the direct method, a statistical analysis is conducted. The result of the pre-test and post-test show a significant improvement in students’ English-speaking abilities by implementing the direct method in the 7th-grade of MTs Negeri 5 Bojonegoro. The limitations of this study regarding the implementation of the direct method in English language learning, specifically in speaking skill, are the resource constraints. A recommendation for further research on the implementation of the direct method in English speaking skills is to focus on observing the role and involvement of teachers in applying the direct method in English speaking instruction.